#y=cos[xy^2]#, differentiaing both side of this expression w.r.t x,
#dy/dx=-sin[xy^2]d/dx[xy^2]# [ chain rule]..........#[1]#
We now need to find #d/dx[xy^2]# using the product rule, i.e,
#d[uv]=vdu+udv#, where #u# and #v# are both functions of #x#, by implicit differentiation.[#v=y^2#and #u=x# in this case]
So #d/dx[xy^2]#=#[y^2+2xydy/dx]#
Therefore #dy/dx=-sin[xy^2][y^2+2xydy/dx]#=#[-y^2sin[xy^2]-[2xysin[xy^2]dy/dx]#
#dy/dx+dy/dx2xysin[xy^2]#=#-y^2sin[xy^2]#
#dy/dx[1+2xysin[xy^2]#=-#y^2sin [xy^2]#,
And so #dy/dx=-y^2sin[xy^2]/[1+2xysin[xy^2]# Hope this was helpful.